In Vivo Foot and Ankle Kinematics During Activities Measured by Using a Dual Fluoroscopic Imaging System: A Narrative Review - Ye, Dongqiang; Sun, Xiaole; Zhang, Cui; Zhang, Shen; Zhang, Xini; Wang, Shaobai; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2021)
Foot and ankle joints are complicated anatomical structures that combine the tibiotalar and subtalar joints. They play an extremely important role in walking, running, jumping and other dynamic activities of the human body. The in vivo kinematic analysis of the foot and ankle helps deeply understand the movement characteristics of these structures, as well as identify abnormal joint movements and treat related diseases. However, the technical deficiencies of traditional medical imaging methods limit studies on in vivo foot and ankle biomechanics. During the last decade, the dual fluoroscopic imaging system (DFIS) has enabled the accurate and noninvasive measurements of the dynamic and static activities in the joints of the body. Thus, this method can be utilised to quantify the movement in the single bones of the foot and ankle and analyse different morphological joints and complex bone positions and movement patterns within these organs. Moreover, it has been widely used in the field of image diagnosis and clinical biomechanics evaluation. The integration of existing single DFIS studies has great methodological reference value for future research on the foot and ankle. Therefore, this review evaluated existing studies that applied DFIS to measure the in vivo kinematics of the foot and ankle during various activities in healthy and pathologic populations. The difference between DFIS and traditional biomechanical measurement methods was shown. The advantages and shortcomings of DFIS in practical application were further elucidated, and effective theoretical support and constructive research direction for future studies on the human foot and ankle were provided.